The Role of Technology in Arabic Education: Smartboard Features and Challenges - M Sholih Salimul Uqba; Nur Hasaniyah; Abdul Muntaqim Al Anshory; Nafiatur Rasyidah (Ihtimam : Jurnal Pendidikan Bahasa Arab, 2024)
This study aims to determine the role of smartboard technology in Arabic language learning media. The approach in this research is descriptive qualitative, which is carried out in the SKS (Semester Credit System) class of MTsN 2 Malang. Data were collected using interview, observation, and documentation techniques. The data were then analyzed with three steps of the Miles and Huberman model, namely, data reduction, data presentation, and conclusion drawing. The findings of this study indicate that the use of smartboard technology has a significant impact on student motivation in learning Arabic. The students report that the incorporation of smartboard technology into the learning environment has increased their interest and enthusiasm in the subject matter. They also perceive a greater sense of involvement in the learning process due to the interactive features of the smartboard, such as writing, drawing, and manipulating objects on the touch screen. Direct interaction with the smartboard in Arabic language learning provides a visual and kinesthetic experience that helps students to understand concepts and develop language skills. However, there are some challenges related to the use of the smartboard, including limited accessibility, infrastructure, and teachers' readiness and competence in integrating the smartboard into learning.